Language Learning Strategies in Online CLIL-Oriented Classrooms: Voices from Indonesian Higher Education Students - Khoiriyah Khoiriyah; Soeparto Soeparto (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. This research aims to analyze the students’ language learning strategies (henceforth LLSs) in online CLIL-oriented classroom and to explore the students’ suggestions toward their online learning in relation to their LLSs. Through a mixed-method, this research involved nineteen students who were enrolled in the psychology department's "International Class" at an Indonesian private university. Strategy Inventory for Language Learning (SILL) questionnaire was distributed followed by conducting semi-structured interview. The finding revealed that all of the participants utilized all of LLSs such as memory strategies, cognitive strategies, metacognitive strategies, affective strategies, and social strategies. Cognitive and metacognitive strategies were considered as the most dominant strategies used during online learning, while affective and social strategies were the least preferable strategies. Based on the student’ response, this might be due to the fact that students are fully responsible for managing the overall learning process and evaluating their learning more frequently to achieve the learning goals, including content knowledge and academic language learning, when using online learning modes, either synchronous or asynchronous, Thus, some suggestions were addressed in terms of lecturers’ scaffolding, structured pre-class activities and collaborative learning. In conclusion, the students adopted high cognitive and metacognitive strategies followed by compensation strategies and other strategies such as social, memory and affective strategies respectively. Yet,CLIL teachers were also suggested to provide online learning activities which also facilitate social strategies as it was deemed by students to have more active participation in online classes. This provides some insight and pedagogical suggestions how EFL teachers or content teachers to facilitate their students to have more effective learning process based on their learning strategies.Keywords: Language Learning Strategies; Online CLIL classroom; Students’ voices